Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The impact of the culture of volunteer work on the behavior of male and female students in public schools in the city of Abha Mrs. Shadiah Naser Al Majthel 2. Circulation of individual and collective theoretical supervisory methods in educational supervisory work Mrs. Ibtihaj A. Al-Bakri 3. The Statues of Job Enrichment among Public School Principals in Hebron Governorate from the teachers’ point of view Mrs. Tagreed Yaser Awawdeh, Dr. Ashraf Mohammad Abu Khayran 4. The Trend towards Specialization and its Relationship to the Anxiety of the Professional future among special education students at Tafila Technical University Mrs. Hadeel Mohammed Al-Hawamdeh, Mrs. Ibtihal Mohammad Al-Khrissat 5. Emotional Intelligence and its Relationship to Life Satisfaction among Secondary School Female Students in Hail region Mrs. Amani Abdullah Aqla Al-Shammari 6. An Integrative approach to treating porn addiction Dr. Heba Jamal Hariri